Effects of Acute Normovolemic Anemia on Hemodynamic Parameters and Acid-Base Balance in Dogs - Champion, Tatiana (SAGE-Hindawi Access to Research, 2011)
The aim of this study was to evaluate the hemodynamic and acid-base status of dogs subjected to acute normovolemic anemia. The dogs (n = 10) were evaluated 15 minutes and 24 hours after induction of anemia (hematocrit below 18%) with blood withdrawal and simultaneously replacement of same volume of Ringer's lactate solution and hydroxyethyl starch-based solution in a 2 : 1 ratio. The cardiac output was measured by Doppler echocardiography and blood pressure by oscillometric device, and posteriorly hemodynamic parameters were calculated. The anemic groups had increase in cardiac index (P < .05) (3.82 ± 1.05 to 5.86 ± 1.49 and 5.81 ± 1.63 L/min × m(2)) and decreases (P < .05) in the indices of total peripheral resistance (6797.81 ± 3060.22 to 3220.14 ± 1275.02 and 3887.74 ± 1394.89 dina·seg/cm(5) × m(2)) and oxygen delivery (7942.84 ± 3344.00 to 4021.68 ± 1627.00 and 4430.82 ± 1402.61 mL/min × m(2)), respectively. There were no significant changes in pH, but PaO(2) and SaO(2) values were increased, and PaCO(2) reduced in anemic dogs (P < .05). Therefore, acute normovolemic anemia can create significant hemodynamic changes and despite some hemogasometric changes, there were no changes in the acid-base status in dogs.